2001
DOI: 10.1161/hh1401.094367
|View full text |Cite
|
Sign up to set email alerts
|

Redox Signaling of the Arteriolar Myogenic Response

Abstract: Arteriolar vascular smooth muscle cells (VSMCs) are mechanosensitive, constricting to elevations in transmural pressure (P TM ). The goal of the present study was to determine using mouse isolated tail arterioles and arteries whether oxidant signaling regulates this myogenic response. In response to P TM elevation, VSMCs of arterioles but not arteries generated constriction and increased reactive oxygen species (ROS) activity (using the H 2 O 2 -sensitive probe dichlorodihydrofluorescein). Arterioles had incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
107
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 18 publications
12
107
0
Order By: Relevance
“…In any case, the involvement of Cx43-based channels in the control of vasomotor tone is consistent with the finding that tensile stretch increased the expression of this connexin as well as gap junction intercellular communication in vascular smooth muscle cells (Cowan et al, 1998). Interestingly, this response was mediated by the formation of reactive oxygen species (Cowan et al, 1998;Cowan et al, 2003), which has been reported to contribute to the initiation of the myogenic constriction in mouse-tail arterioles (Nowicki et al, 2001). …”
Section: Gap Junctions In Vascular Smooth Musclesupporting
confidence: 86%
“…In any case, the involvement of Cx43-based channels in the control of vasomotor tone is consistent with the finding that tensile stretch increased the expression of this connexin as well as gap junction intercellular communication in vascular smooth muscle cells (Cowan et al, 1998). Interestingly, this response was mediated by the formation of reactive oxygen species (Cowan et al, 1998;Cowan et al, 2003), which has been reported to contribute to the initiation of the myogenic constriction in mouse-tail arterioles (Nowicki et al, 2001). …”
Section: Gap Junctions In Vascular Smooth Musclesupporting
confidence: 86%
“…The data presented in Figure 2 indicated that H 2 O 2 production is an important mediator of NF-〉 activation in endothelial cells. Importantly, we found that high pressure can elicit significant increases in vascular H 2 O 2 generation, 34 likely by activation of NAD(P)H oxidase ( Figure 4F). 15 The view that high pressureinduced NAD(P)H oxidase may initiate NF-〉 activation in endothelial cells even in the absence of proinflammatory cytokines is supported by the finding that high pressure-induced activation of NF-〉 was decreased significantly by DPI ( Figure 4G).…”
Section: Discussionmentioning
confidence: 85%
“…Rac1, which belongs to the small GTPase protein superfamily, participates in the regulation of NADPH oxidase in numerous cell types. 44 We were surprised to find that L-arginine decreases Rac1 at the levels of mRNA as well as protein in renal cortex of DS rats ( Figures 4D and 5C). Taken together, these actions of L-arginine, which appear to interfere with translocation of p47phox to the membrane fraction and to downregulate total expression levels of gp91phox as well as Rac1, may contribute to decrease overall enzyme activity of renal NADPH oxidase in high salt-loaded animals.…”
Section: Discussionmentioning
confidence: 91%